FREQUENCY OF RETINOPATHY AMONG DIABETICS ADMITTED IN A TEACHING HOSPITAL OF LAHORE - Kayani, Huma; Rehan, N.; Ullah, Naeem (Journal of Ayub Medical College Abbottabad, 2003)
Background: Diabetic retinopathy is a complication of diabetes that affects the blood vessels of the retina and leads to blindness. Although 4 - 8 million diabetics exist in Pakistan, very little work has been done on this complication of diabetes. The present study was undertaken to estimate the frequency of retinopathy among diabetics admitted in a teaching hospital of Lahore. Methods: Every patient of diabetes mellitus, admitted in departments of Medicine, Surgery, Ophthalmology and Obstetrics & Gynecology at Sir Ganga RamHospital, Lahore between June 2001 and September 2001 was included in the study. After adequate mydriasis, detailed fundus examination using indirect opthalmoscope was carried out to determine the presence of diabetic retinopathy and its type. Results: Out of 4414 admissions, 540 patients - 340 females and 196 males were diabetics. Among 540 diabetics, 132 had Type-1 diabetes (24.4%) while 408 had Type-2 diabetes (75.6%). The duration of diabetes ranged from 10 to 12 years. The prevalence of diabetes among admitted patents was 12.2%. Among these 540 diabetics, 180 had diabetic retinopathy showing a prevalence of 33.3%. Non-proliferative retinopathy was present in 21.5% diabetics and proliferative retinopathy among 11.8% diabetics. The prevalence of retinopathy was significantly higher (P<0.001) among males (42.8%) as compared to females (27.9%). The prevalence was similar (33.3%) among both Type-1 as well as Type-2 diabetes as well as similar to that reported from other countries. Conclusion: Since 33.3% of our diabetic population is suffering from retinopathy - a condition amenable to timely and cost-effective treatment, every diabetic should be made aware of the importance of regular ophthalmologic examination.